2006
DOI: 10.1007/s10620-006-3174-3
|View full text |Cite
|
Sign up to set email alerts
|

Zonation of Hepatic Bile Salt Transporters

Abstract: Pericentral and periportal hepatocytes differ in their capacity to eliminate and velocity of eliminating bile acids and other organic anions. We wonder whether differences in the distribution of anion transporters (ntcp [M77479], besp [NM_031760], mrp2 [NM_012833], oatp1 [NM_017111], oatp2 [NM_131906]) cause the differences in bile acid excretion. Therefore, we analyzed the distribution of these anion transporters in periportal and pericentral cells by immunohistology, their mRNA by quantitative PCR, and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
(24 reference statements)
0
17
1
1
Order By: Relevance
“…Several sinusoidal membrane transporters (3,8) e.g., sodium-dependent taurocholate cotransporting polypeptide (Ntcp/Slc10a1), and organic anion transporting polyeptides (oatp1a1/Slco1a1, oatp1a4/Slco1a4, oatp1b2/Slco1b2), accept unconjugated bile acids as substrates (9,11,23,26). Their distributions are zonated to the liver as is the case for GAT2: even an acinar distribution for Ntcp and oatp1a1 (3), and pericentral hepatocyte-predominant expression for oatp1a4 (34) and oatp1b2 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Several sinusoidal membrane transporters (3,8) e.g., sodium-dependent taurocholate cotransporting polypeptide (Ntcp/Slc10a1), and organic anion transporting polyeptides (oatp1a1/Slco1a1, oatp1a4/Slco1a4, oatp1b2/Slco1b2), accept unconjugated bile acids as substrates (9,11,23,26). Their distributions are zonated to the liver as is the case for GAT2: even an acinar distribution for Ntcp and oatp1a1 (3), and pericentral hepatocyte-predominant expression for oatp1a4 (34) and oatp1b2 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identification and func- tional studies showed the transport of the unconjugated form of bile acid by bile acid transporters expressed at the sinusoidal membrane. [73][74][75][76] The reconjugation of taurine and de novo synthesis of taurine-conjugated bile salts have recently been suggested to occur through the coupling of oatp1a1 (Slco1a1), Ntcp (Slc10a1) and GAT2 in periportal hepatocytes, because of their acinar distribution and pericentral-dominant expression of oatp1b2 (Slco1b2) and oatp1a4 (Slco1a4). [74][75][76] 6.…”
Section: Hepatic Taurine Uptake Mediated By Gat2mentioning
confidence: 99%
“…[73][74][75][76] The reconjugation of taurine and de novo synthesis of taurine-conjugated bile salts have recently been suggested to occur through the coupling of oatp1a1 (Slco1a1), Ntcp (Slc10a1) and GAT2 in periportal hepatocytes, because of their acinar distribution and pericentral-dominant expression of oatp1b2 (Slco1b2) and oatp1a4 (Slco1a4). [74][75][76] 6. STRUCTURAL BASIS OF TAURINE AND GABA TRANSPORT BY TAUT Among Na + -and Cl − -dependent transporters belonging to SLC6A family, TauT is reported to have a lower affinity (1.5 mM) for GABA than GATs (<80 µM), 10,11) while the amino acid sequence of GATs is similar to that of TauT, 77,78) and the molecular basis of this different affinity has been an important topic in understanding the substrate specificity of SLC6A family members.…”
Section: Hepatic Taurine Uptake Mediated By Gat2mentioning
confidence: 99%
“…84 In the gradient type, all hepatocytes are able to express a particular gene, but the level of expression depends on the position of the hepatocyte along the portocentral radius. Examples include key regulatory enzymes of carbohydrate metabolism, cytosolic phosphoenol-pyruvate carboxykinase I (PCK) and glucokinase.…”
Section: Regulation Of the Hepatic Microcirculationmentioning
confidence: 99%
“…In the case of bile formation, physiological availability of biliary solutes in periportal blood is a major determinant, independent of hepatocellular expression of relevant transporters. 84 Likewise, gradients of oxygen and hormones across the lobule are thought to play key roles influencing expression of metabolic enzymes. 80 Recently, it has been shown that the Wnt/β-catenin signalling pathway plays a key role in regulating liver zonation.…”
Section: Plasma Membranementioning
confidence: 99%